Does interset stretching change the autonomic modulation and hemodynamic responses in trained young men? - Miranda, Lucas Rangel Affonso de; Reis, Carlos Brendo Ferreira; Oliveira, Matheus Agnez de; Mello, Igor Alves; Pinto, Leandro Moraes; Mostarda, Cristiano Teixeira; Bocalini, Danilo Sales; Leite, Richard Diego (Revista Brasileira de Educação Física e Esporte, 2023)
The aim of the present study was to analyze the effect of interset stretching in the heart rate variability and hemodynamic responses. The sample consisted of 8 trained men (23 ± 2.72 years, 1.74 ± 0.07 meters, 75.66 ± 10.85 kg). The lower limbs training protocol started with three sets of 10 maximal repetitions in the back squat and leg press exercises, with 1-minute rest between sets. After that, 7 sets of maximal repetitions were performed on the leg extension machine with 30 seconds interval between sets, using the first 20 seconds for passive stretching of the quadriceps muscles. Hemodynamic responses and autonomic modulation were obtained at rest, during the session and immediately after for 15 minutes post-session. Autonomic modulation was monitored by heart rate variability. Significant reductions during and after resistance training protocol were observed for RR intervals, RMSSD, pNN50, SDNN, 2LV%, 2UV%, LF and HF in comparison with basal levels. Meanwhile, 0V% presented significantly increases during and after experimental protocol. Lower LF/HF, LFnu and HFnu values was observed during protocol. Systolic blood pressure (SBP), mean blood pressure (MBP), heart rate (HR) and rate pressure product (RPP) were significantly higher after session. After 15 minutes, SBP, DBP, MBP, and RPP returned to near baseline values. The sympathetic activity increased during the protocol and post 15 minutes.